Eavesdropping at the Speed of Light: Distributed Acoustic Sensing of Baleen Whales in the Arctic - Bouffaut, Léa; Taweesintananon, Kittinat; Kriesell, Hannah J.; Rørstadbotnen, Robin A.; Potter, John R.; Landrø, Martin; Johansen, Ståle E.; Brenne, Jan K.; Haukanes, Aksel; Schjelderup, Olaf; Storvik, Frode (Frontiers in Marine Science, 2022)
In a post-industrial whaling world, flagship and charismatic baleen whale species are indicators of the health of our oceans. However, traditional monitoring methods provide spatially and temporally undersampled data to evaluate and mitigate the impacts of increasing climatic and anthropogenic pressures for conservation. Here we present the first case of wildlife monitoring using distributed acoustic sensing (DAS). By repurposing the globally-available infrastructure of sub-sea telecommunication fiber optic (FO) cables, DAS can (1) record vocalizing baleen whales along a 120 km FO cable with a sensing point every 4 m, from a protected fjord area out to the open ocean; (2) estimate the 3D position of a vocalizing whale for animal density estimation; and (3) exploit whale non-stereotyped vocalizations to provide fully-passive conventional seismic records for subsurface exploration. This first example’s success in the Arctic suggests DAS’s potential for real-time and low-cost monitoring of whales worldwide with unprecedented coverage and spatial resolution.